Haida grammar [electronic resource] - Harrison, C. (Charles), Rev.; Royal Society of Canada. (Ottawa : For sale by J. Durie; Toronto : Copp-Clark, 1895)
Tables. Some text in Haida. Cover title. "From the Transactions of the Royal Society of Canada, 2nd ser., v. 1. section 2, 1895-96." Electronic reproduction. Mode of access: Internet. 44